Novel Aggregation Promoting Factor AggE Contributes to the Probiotic Properties of Enterococcus faecium BGGO9-28 - Veljović, Katarina; Popović, Nikola; Miljković, Marija; Tolinački, Maja; Terzić-Vidojević, Amarela; Kojić, Milan (Frontiers in Microbiology, 2017)
The understanding of mechanisms of interactions between various bacterial cell surface proteins and host receptors has become imperative for the study of the health promoting features of probiotic enterococci. This study, for the first time, describes a novel enterococcal aggregation protein, AggE, from Enterococcus faecium BGGO9-28, selected from a laboratory collection of enterococcal isolates with auto-aggregation phenotypes. Among them, En. faecium BGGO9-28 showed the strongest auto-aggregation, adhesion to components of ECM and biofilm formation. Novel aggregation promoting factor AggE, a protein of 178.1 kDa, belongs to the collagen-binding superfamily of proteins and shares similar architecture with previously discovered aggregation factors from lactic acid bacteria (LAB). Its expression in heterologous enterococcal and lactococcal hosts demonstrates that the aggE gene is sufficient for cell aggregation. The derivatives carrying aggE exhibited the ten times higher adhesion ability to collagen and fibronectin, possess about two times higher adhesion to mucin and contribute to the increase of biofilm formation, comparing to the control strains. Analysis for the presence of virulence factors (cytolysin and gelatinase production), antibiotic resistance (antibiotic susceptibility) and genes (cylA, agg, gelE, esp, hylN, ace, efaAfs, and efaAfm) showed that BGGO9-28 was sensitive to all tested antibiotics, without hemolytic or gelatinase activity. This strain does not carry any of the tested genes encoding for known virulence factors. Results showed that BGGO9-28 was resistant to low pH and high concentrations of bile salts. Also, it adhered strongly to the Caco-2 human epithelial cell line. In conclusion, the results of this study indicate that the presence of AggE protein on the cell surface in enterococci is a desirable probiotic feature.